Antiviral Therapy of Symptomatic HCV-mixed Cryoglobulinemia after Liver Transplant: Case Report and Literature Review. Issue 5 (May 2013) - Donato, Maria Francesca; Banfi, Giovanni; Cresseri, Donata; Fogazzi, G. Battista; Martin, Paul; Messa, Piergiorgio; Fabrizi, Fabrizio
Hepatitis C virus (HCV) infection may be associated with extra-hepatic illness including mixed cryoglobulinemia (MC). Consistent evidence exists on HCV-MC in the non-transplantation setting but information on HCV-related cryoglobulinemia after solid organ transplantation is limited, particularly after liver transplantation (LT). We report on a 48-year-old man who developed HCV-associated cryoglobulinemic vasculitis with recurrent hepatitis after liver transplant. One year after transplant for HCV-positive cirrhosis, he presented severe cutaneous manifestations, and biopsy-proven cryoglobulinemic membrano-proliferative glomerulonephritis (MPGN). HCV RNA clearance occurred within a few weeks of antiviral therapy; sustained viral response (SVR) was obtained by one year of anti-HCV combination therapy (eight months of pegylated IFN/ribavirin and four months of standard IFN/ribavirin). SVR was linked to complete remission of skin, liver, and kidney abnormalities. Tolerance to the pegylated IFN/ribavirin regimen was not excellent due to the occurrence of lobar pneumonia with anemia; thus, peg-IFN was replaced by recombinant IFN, with a favorable outcome. Clinical and viral remission persisted over a 48-month follow-up. HCV-associated mixed cryoglobulinemia flareups following LT were successfully managed with combined antiviral therapy. HCV-related MC is uncommon in developed countries and this clearly hampers randomized controlled clinical trials aimed at evaluating the efficacy and safety of anti-HCV therapy after solid organ transplantation or in the non-transplantation setting.